Nietzsche e Rosset: alegria, impulso à criação - Campos Júnior, Lindoaldo Vieira (2013)
Understood in a project of transvaluation of values, the joy is one of the central themes of the thought of Friedrich Nietzsche and Clément Rosset. Opposed to the dogmatic philosophy that moralize and robs your strength to think of it as "happiness", evaluated, in short, a target linked to virtue and rationality these thinkers propose a perspective that makes the joy of point to an instance extraterrestrial and back to the earth, to the body. In this vein, beyond the oppositions of values constitutive of metaphysics dogmatic, the joy and suffering are conceived as elements that are not mutually exclusive, they are complementary as foundations of a gaia(ta) science, based in laughter and friendship. Contents of a tragic wisdom that leads to an unconditional fidelity to the real (expressed in formulas of amor fati Nietzsche and unrestricted approval of existence Rosset), the joy is then interview as vital impulse, the force majeure, the strength plastic encourages artistic creation: the joy of children playing